RUSSIA’S PLACE ON THE WORLD COAL MARKET - I. Moga (Вестник университета, 2018)
The current situation in the global coal market, based on data for the last few years and the place of Russia in this market is described. The main provisions of the state policy of the Russian Federation, the volume and direction of foreign trade in coal, the prospects and forecasts of the world coal market are considered. The relevance of the topic is determined by the severity of the problems of world energy supply and changes in the position of the Russian Federation in international coal trade as a result of the active formation of new world coal centers.